Roots Induction and Growth of Shoot Cutting of Jirak (Eurya acuminata DC.) by Adding Some Growth Regulator Solutions in Various Planting Medium - Gupitasari, Tressa Pratywi; Noli, Zozy Aneloi; Suwirmen, Suwirmen (Metamorfosa: Journal of Biological Sciences, 2019)
The research about roots induction and growth of shoot cutting of Jirak ( Eurya acuminata DC.) by adding some growth regulator solutions in various planting medium, was conducted from May until August 2017 in Greenhouse and Plant Physiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Science, Andalas University. The aims of the research to find out effect of  providing growth regulator solution with different types, used of planting medium and interaction of both factors the best to roots induction and growth Jirak ( E. acuminata DC.) by cutting. The research used Complete Randomized Design (CRD) factorial with two factors and three replications. Factors A were  growth regulator solution (a0: control, a1: IBA 100 ppm, a2: NAA 100 ppm, a3: IAA 100 ppm) and factors B were various planting medium (b0: garden soil, b1: sand, b2: charcoal husk). The research result were adding some growth regulator solutions and various planting medium significanly affected roots induction and growth of jirak and there is interaction on the high of plant. The treatment of 100 ppm IAA and treatment using sand medium obtain the highest result in increasing roots induction and growth of shoot cutting of Jirak.